A mouldable fibreglass backslab device as a novel approach to offload chronic plantar foot ulcers: A retrospective observational audit - Melissa Ting; Ivana Ferreira; Jonathan Hiew; Mahalia McEvoy; Gabrielle Tan; Priyal Shah; Eugenie Nicolandis; Emma J. Hamilton; Jens Carsten Ritter; Michael Nicolaou; Laurens Manning (Journal of Foot and Ankle Research)
Abstract Background Pressure offloading is a critical component of plantar foot ulcer management, including diabetes‐related foot ulcers (DFU). Conventional offloading options such as total contact casting and removable knee‐high walkers may be unsuitable or unsuccessful in patients with morbid obesity, intermittent lower limb oedema, high exudative wounds or poor mobility. A mouldable fibreglass backslab device (BSD) may be a practical alternative to be considered in these situations. Methods Data were retrospectively collected on 28 patients (29 foot ulcers) with non‐healing ulcers who received a BSD to offload their foot ulcer as an extension to standard offloading care. Baseline data included: patient demographics, type of offloading prior to BSD application, date of ulcer onset, days ulcer present prior to BSD application and ulcer size at BSD initiation. Measures of success included ulcer size reduction 12 weeks post‐BSD application, time to complete ulcer healing in BSD, time to 50% reduction in ulcer size post‐BSD application and total number of days ulcer present. Results The median (IQR) ulcer area and ulcer duration at baseline for 19 patients (20 ulcers) who used the BSD was 1.65 (0.4–3.8) cm2 and 531 (101–635) days. At 12 weeks, the median (IQR) ulcer area was 0.3 (0–0.55) cm2 with a median (IQR) reduction of 97 (80–100) %. Nine (45%) ulcers achieved complete wound healing (100% reduction in wound size) at 12 weeks post‐BSD application, and the remaining 11 (55%) ulcers achieved at least 50% reduction in wound size. The median (IQR) time to complete wound healing and 50% reduction in wound size was 71 (35–134) days and 24 (15–44) days, respectively. Nine patients ceased use of the BSD and reverted to conventional offloading before their wounds had healed. Of these, four patients achieved a 50% reduction in wound size at the 12‐week mark with conventional offloading. Conclusion Our preliminary data suggests that a mouldable fibreglass BSD may be a practical offloading option in the management of DFUs, especially when conventional offloading methods are unsuccessful, unsuitable or unacceptable to patients. Higher level evidence is required to demonstrate suitability or efficacy of the BSD compared to current evidence‐based recommended offloading methods.